Flower traits and breeding system of Rhododendron platypodum diels, an endangered plant species in China - Chaoying Wang; Yingzan Xie; Lihui Ma (PLoS ONE, 2025)
Rhododendron platypodum Diels is an endangered ornamental plant distributed in the high-elevation subtropical regions of China. Known as one of the “queen flower”, its population is restricted to three sites in China, with only few individuals. To explore the reasons for poor population regeneration and provide theoretical basis for genetic breeding to support its popularization and application of this native garden tree species, field investigation and artificial pollination experiment were conducted to test the flowering characteristics and breeding system of R. platypodum in Zhaoyun Mountain, Chongqing. The results revealed that: (1) the flowering period of R. platypodum began in mid-April and ended in late May, lasting 36 days, with an average flowering duration of 9.15 days per flower. (2) Pollen viability was highest in the morning and evening, peaking on third day after flowering, while stigma receptivity was highest between the second and third days. (3) The value of hybridization index and the pollen-ovule ratio indicated a partial self-compatibility and facultative outbreeding of this species. (4) Artificial pollination experiments showed no evidence of parthenogenesis or automatic self-pollination, and the fruit set rates for xenogamy, geitonogamy were higher than those for self-pollination, with artificial pollination yielding higher fruit set rate than natural pollination. (5) The primary effective pollinators of R. platypodum were identified as Bombus sp. and Apis cerana sinensis. Our research found that instead of long flowering period, high pollen viability and simultaneous mature of stigma and pollen, high geitonogamy relying on pollinators for effective production and the pollen restriction are more likely to have adverse effects on the population of R. platypodum. Further factors such as limitation in seed dispersal, germination challenges, and environmental requirement for seedlings and saplings may contribute to the endangerment of R. platypodum.